2007
DOI: 10.1111/j.0014-3820.2001.tb00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Structure and Hierarchical Genetic Diversity in the Brook Charr, Salvelinus Fontinalis

Abstract: Explaining the extent, causes, and consequences of biotic distributions in space is fundamental to our understanding of how species evolve and cope with particular environments. Yet, identifying extrinsic barriers to migration imposed by landscape structure and predicting their impacts on intraspecific genetic diversity remains a major challenge in population biology. In this study, 30 populations (771 individuals) of brook charr (Salvelinus fontinalis, Salmonidae) representing six major river drainages from M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
106
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 75 publications
11
106
5
Order By: Relevance
“…For example, upstream populations tended to have less genetic variability than the corresponding downstream population (Table 1). This pattern is consistent with studies in other fishes, including mosquitofish, Gambusia holbrooki (Hernandez-Martich and Smith, 1990); brown trout, Salmo trutta (Hamilton et al, 1989) and brook charr, Salvelinus fontinalis (Castric et al, 2001). The pattern probably reflects more pronounced founder effects and smaller population sizes associated with upstream populations as well as lower immigration due to unidirectional downstream gene flow (Shaw et al, , 1994Crispo et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, upstream populations tended to have less genetic variability than the corresponding downstream population (Table 1). This pattern is consistent with studies in other fishes, including mosquitofish, Gambusia holbrooki (Hernandez-Martich and Smith, 1990); brown trout, Salmo trutta (Hamilton et al, 1989) and brook charr, Salvelinus fontinalis (Castric et al, 2001). The pattern probably reflects more pronounced founder effects and smaller population sizes associated with upstream populations as well as lower immigration due to unidirectional downstream gene flow (Shaw et al, , 1994Crispo et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…The first involves topographical features including water connectivity and barriers that can affect contemporary dispersal (Castric et al, 2001;Crispo et al, 2006;Caldera and Bolnick, 2008). The second involves adaptive divergence under variable selection pressures whereby dispersers or hybrids tend to have lower fitness than residents and gene flow between ecological environments can thus be impeded (Lu and Bernatchez, 1999;Ogden and Thorpe, 2002;Rundle, 2002;reviewed by Schluter, 2000;Hendry, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research using this experimental design found predictable patterns of genetic variation of fish and invertebrate species in watersheds on the basis of their ability to ascend stream gradients and migrate over long distances (Monaghan et al 2002;Whiteley et al 2004;de Kerckhove 2005). Another promising approach would be the study of the same organism in different landscape arrangements (e.g., Castric et al 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although suitable Arctic char habitat has not been quantified directly in both systems, Roux et al (2011b) suggest that Brock Lake has low productivity and relatively limited fish habitat potential primarily because of its small size (2.5 km ). This situation has implications for Arctic char carrying capacity, and several studies have documented associations between habitat size and population size (Frankham, 1996;HĂ€nfling and Brandl, 1998;Castric et al, 2001). Although abundance estimates are not available for the Brock system, Roux et al (2011b) suggested, on the basis of low catch-per-unit-effort (CPUE), that the population is likely very small.…”
Section: Mixed-stock Analysis Of Darnley Bay Arctic Charmentioning
confidence: 99%